Manipulating levels of uncertainty in a decision-making task for obsessive compulsive disorder - Uma Maheswari Ganesh; Lavanya Sharma; Himani Kashyap; Shyam Sundar Arumugham; Janardhan Reddy (Brazilian Journal of Psychiatry)
Objective: We investigated whether manipulating levels of uncertainty would influence performance in a decision-making task in people with obsessive-compulsive disorder. Methods: This case-control study compares Beads Task (measuring reflection/decisional impulsivity) performance and trait impulsivity (Short Urgency-Premeditation-Perseverance-Sensation Seeking-Positive Urgency [UPPS-P] Impulsive Behavior Scale) in patients with obsessive-compulsive disorder (n = 65) and non-clinical controls (n = 45). Differences between groups were assessed with the Mann Whitney U test. Results: The obsessive-compulsive disorder group had significantly fewer draws to decision (U = 1,845, p = 0.019) and less subjective decision-certainty (U = 1,518, p = 0.00) in the low uncertainty (85:15) condition, and higher negative urgency scores (U = 2,163, p ≤ 0.001) and lower sensation-seeking scores (U = 907.5, p = 0.001) in UPPS-P. However, differences in Beads Task performance did not survive correction for multiple comparisons. Conclusion: Patients with obsessive-compulsive disorder engage in more impulsive decision-making in the lower uncertainty condition than healthy controls, despite low subjective certainty of the decision. They also had higher scores for the trait impulsivity factor of negative urgency. Future studies should explore the contribution of trait impulsivity, as well as symptom severity, anxiety, and decision-certainty, to impulsivity in obsessive-compulsive disorder.